Lomba Melukis dan Mewarnai sebagai Wahana Edukasi dan Promosi Wisata Edukasi Jowaran Desa Jambuwer - Andi Wibowo; Wuli Oktiningrum; Dyah Ayu Pramoda Wardhani; Adzimatnur Muslihasari; Angga Dwi Prassetio (I-Com: Indonesian Community Journal, 2024)
Painting and coloring competition activities at kindergarten and elementary school levels aim as a means of education and promotion of Jowaran educational tourism in Jambuwer Village. This activity was attended by participants and also accompanied by the participants' parents. The kindergarten coloring competition was attended by 36 kindergarten students and accompanied by their respective parents. The elementary school painting and coloring competition was attended by 13 elementary school students and also accompanied by their respective parents. The painting and coloring competition will be held on Sunday, January 28 2024 from 07.00 to 13.00 with the theme of natural scenery. Procedures for implementing activities are planning, implementation and evaluation. The result of this activity is that it can increase tourist visits to Jowaran educational tourist attractions. Jowaran educational tourism, which previously had few visitors, is now getting more and more visitors.